Pengaruh Gadget pada Karakter Anak di SD - Yusnadi Yusnadi; Trisna Rukhmana; Nana Sujana; Sepryanus Rano Putra; Aat Ruchiat Nugraha; Diana Arianti (Journal on Education, 2024)
This research aims to analyze and explain the influence of gadget use on the character of children in elementary school (SD). In today's digital era, gadget use is becoming increasingly common among children, which raises questions about its impact on their character development and mental health. This research uses a qualitative approach, by collecting data through in-depth interviews with parents, teachers and children in elementary schools, as well as direct observation of gadget use in the school and home environment. The research results show that excessive use of gadgets can affect children's psychological development, including anxiety, difficulty in managing emotions, and dependence on technology. However, the use of gadgets can also support the development of children's creativity and adaptive abilities. This research emphasizes the importance of a balanced and responsible approach to children's use of gadgets, with the aim of developing balanced social and emotional skills, as well as preventing negative impacts on their health.